Correlation of Wharton‘s Jelly with Birth Weight of Neonate of Pre-gestational and Gestational Diabetic Mother (Bangladesh Journal of Anatomy, 2014)
Context: The umbilical cord appears to have organ -like properties containing two arteries and one vein covered by a connective tissue called Wharton’s jelly. Wharton’s jelly holds the vessels together, regulate blood flow, plays a role in providing nutrition to the fetus and stores chemical substances for the onset of labour. The umbilical cord without much Wharton’s jelly is prone to compression and complete absence is usually associated with fetal death. Gestational diabetes mellitus (GDM) is a common metabolic disorder One of the most relevant consequence of maternal gestational diabetes is excessive or accelerated growth of the fetus. For this reason, the present study was aimed at finding the correlation of the Wharton’s jelly area of the umbilical cord with birth weight of neonate of Pre-gestational and Gestational diabetic mother and to find out any deviation from the controls.Materials and Method: The study was cross-sectional, analytical and observational type which was carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka between July 2004 and December 2005. A total number of 60 Umbilical cords with placentae were collected within 34 to 40 weeks of gestation from BSMMU and BIRDEM. Among these, twenty were from mothers not suffering from diabetes(Control group), twenty had pre-gestational diabetes mellitus(PDM group) and twenty were suffering from gestational diabetes mellitus (GDM group). The umbilical cord cross-sectional area, vessel area and Wharton’s jelly area were measured.Results: Wharton’s jelly area showed significant positive correlation with birth weight of neonate in all the three groups. But there was no significant difference between birth weight of neonates in the three groups.Bangladesh J. Anat. 2014; 12(2) : 51-55